Beginning Object-Oriented ASP.NET 2.0 with VB .NET From Novice to Professional - Myers, Brian; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
Beginning Object-Oriented ASP.NET 2.0 with VB .NET covers all of the basics, from definition to inheritance. This book even includes a chapter on Visual Studio 2005 and Microsoft .NET Framework 2.0, enabling you to create ASP.NET 2.0 applications. Also included are chapters on creating web forms, web controls, and web services. Code samples illustrate the usage of each concept.
An Introduction to .NET and Visual Studio 2005 -- Object-Oriented Programming -- Attributes and Actions -- Encapsulation -- Inheritance -- Namespaces -- Class Design -- ASP.NET Web Forms -- ASP.NET Controls -- Web Services.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems